2015
DOI: 10.1016/j.rser.2015.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Power to liquid and power to gas: An option for the German Energiewende

Abstract: The large-scale deployment of renewable energy sources (RES) is an important aspect of decarbonising the energy supply, and represents a key part of the German Energiewende. However, significantly increasing the share of renewable power in the energy mix implies coping with the natural intermittency of RES like wind and solar. RES development also does not directly address non-electric energy needs such as fuels for transportation and industry feedstock, which are presently relying on fossil fuels. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
116
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(123 citation statements)
references
References 38 publications
0
116
0
7
Order By: Relevance
“…Global energy demand is expected to double by 2050 [1]. More than 80% of global energy demand is still satisfied by fossil fuels due to their abundance and availability [2].…”
Section: Introductionmentioning
confidence: 99%
“…Global energy demand is expected to double by 2050 [1]. More than 80% of global energy demand is still satisfied by fossil fuels due to their abundance and availability [2].…”
Section: Introductionmentioning
confidence: 99%
“…This can be compared to the CO2 capture cost linked to processes requiring an extra purification step like steel and iron, ammonia, refinery, cement, and fossil or biomass combustion plants estimated at 20€2015-170€2015/ ton CO2 in the short term (10-15 years) and 10€2015-100€2015/ton CO2 in the more long term (Damen et al, 2007;Finkenrath, 2011;Kuramochi et al, 2012Kuramochi et al, , 2013IEA, 2013). Even though it has been indicated that the cost for carbon capture represents a relatively modest share (a few percent) of the total electrofuel-production cost unless air capture is assumed (Graves et al, 2011;Tremel et al, 2015;Varone and Ferrari, 2015; see text footnote 1), using CO2 from biofuel production represent an attractive source for electrofuel production since more pure streams will likely be used first for economic reasons and the domestic biofuel actors, representing a considerable biofuel production capacity, in order to comply with sustainability requirements need to improve their production processes in terms of CO2 emissions. Table 1 presents the type of CO2 stream, typical concentration of CO2, the range of CO2 emissions per unit, and the amount of recoverable CO2, for different point sources.…”
Section: Methodsmentioning
confidence: 99%
“…Interest in electrofuels is on the rise, both in the literature (Graves et al, 2011;Mohseni, 2012;Nikoleris and Nilsson, 2013;Taljegård et al, 2015) 1 and in terms of demonstration plants in the EU, in some cases, including CO2 capture (Gahleitner, 2013). Studies mainly investigate electrofuels as a (i) technology for storing intermittent electricity [e.g., Streibel et al (2013), de Boer et al (2014, Vandewalle et al (2014), König et al (2015), Qadrdan et al (2015), Varone and Ferrari (2015), Zakeri and Syri (2015), Zhang et al (2015), and Kötter et al (2016)], (ii) fuel for transport [e.g., Connolly et al (2014), Ridjan et al (2014), Larsson et al (2015)], or (iii) means of producing chemicals [e.g., Ganesh (2013), Perathoner and Centi (2014), and Chen et al (2016)]. Different types of energy carriers [e.g., methane, methanol, DME (dimethyl ether), gasoline, and diesel] can be produced, which makes electrofuels a potentially interesting option for all transport modes, especially shipping, aviation, and long distance road transport, where the potential for other renewable fuel options, such as electricity and hydrogen, may be limited.…”
mentioning
confidence: 99%
“…The value of C M varies depending on the sources of carbon dioxide, and the expenditure for carbon dioxide approximately ranges from 10 $/t to 1000 $/t, and the coefficient a is approximately 0.2 t/MWh [8,18,27]. Figure 2 compares the income, revenue and cost compositions of PtG plants with C M price at 10 $/t (e.g.…”
Section: Independent Operationsmentioning
confidence: 99%
“…The cost of carbon sources also becomes nonnegligible with the increase of C M . The cost of carbon dioxide is somewhat very complicated to quantify and out of the scope of this paper [27]. Thus, the influences of C M will be omitted and no further discussions will be included in the rest part of this paper.…”
Section: Independent Operationsmentioning
confidence: 99%